Central African Republic Country Environmental Analysis : Environmental Management for Sustainable Growth - World Bank (World Bank, Washington, DC, 2020)
The objectives of this Country Environmental Analysis (CEA) for the Central African Republic, are to provide an analytical basis for the development of policy recommendations, assist in defining priority investments to address the most significant environmental management challenges, and inform decision-making in relation to the achievement of sustainable economic growth. This analysis consists of three components, the first being an identification and estimation of the principal sources, costs, and trends, of environmental degradation. This is followed by an analysis of the current institutional capacity for environmental management. Finally, priority environmental issues are analysed, leading to a set of policy and investment recommendations. The three most important priorities are: environmental management in the mining sector; management of forests and wildlife resources; and promoting growth that is resilient to climate change. Two generic CEA tasks were also undertaken: an analysis of the costs of environmental degradation, and an assessment of institutional capacity for environmental management. Recommendations for policy, investment, and technical assistance are presented as short, medium, or long term priorities, in table format, together with an indication of the primary responsibility for each action, and an initial budget estimate for the investment, and technical assistance recommendations.